Simplified Immuno-assay for Rapid Label-free Dengue Serotype Diagnosis: Suppression of Non-specific Binding Interference. (2017) - Loureiro, F.C.L.; Lima, A.M.N.; Roque, R.; de Figueiredo, R.M.P.; Melcher, E.U.K.; Borre, M.; Thirstrup, C.; Neff, H.
Abstract: An easy to implement immunoassay for rapid dengue virus (DENV) serotype diagnosis in the early infection stage is reported. The four-layer assay is immobilized onto a thin gold film and relies on a polymer biochip for optical surface plasmon resonance sensing and detection. The protocol comprises Neutravidin-Biotin mediated DENV monoclonal antibody (MABD ) attachment as the functionalized sensing element. The MABD -DENV complex formation results in a pronounced thickness change that is optically detected in real time. The protocol is applicable in presence of strong non-specific binding interference. False positive indications for negative serum and blood control samples were not observed. The method can be modified towards detection of other viruses infections.